Procalcitonin levels in patients with suspected sepsis - Goswami, Tribeni; Mathew, Renu; Thomas, Marina; Jose, Reena Anie; Jacob, Anjali; Abraham, Sherin Susan (Asian Journal of Medical Sciences, 2021)
Background: Procalcitonin (PCT) was found to be a valuable and reliable biomarker for sepsis, especially in critical care patients for whom early recognition and prompt treatment could reduce mortality. Aims and Objectives: This study was aimed at correlating the levels of PCT as diagnostic marker for sepsis in relation to the culture positivity of various samples from blood, respiratory, urine, and exudates from patients admitted in a tertiary care hospital. Materials and Methods: Results of PCT level along with bacterial culture results of blood, respiratory, urine, and exudates were analyzed from 780 patients for a period of 1 year. Results: High PCT values ranging from 0.52 to 200 ng/ml were found in 331 patients admitted with suspected sepsis. Out of 135 cases of sepsis, 85 had blood culture positivity alone and 50 had culture positivity in blood and in other sites with the same organism. Among the 85 cases of bloodstream infections, in which no localized infections were identified, the median PCT was 33 for Gram-negative bacteremia, which was significantly higher as compared with a median of 16 for Gram-positive cocci. In UTI with bacteremia, the median PCT was 45.34 and in UTI without bacteremia, it was 5. Conclusion: From this study, we concluded that PCT values may be useful to distinguish Gram-negative and Gram-positive bacteremia, and furthermore, a high PCT value for patients with UTI may be helpful in predicting bacteremia.